KONSEP TEORI PENYADARAN PAULO FREIRE SEBAGAI ALTERNATIF PEMECAHAN MASALAH PENDIDIKAN ANAK JALANAN DI INDONESIA - Restiawan Permana (Universitas Bina Sarana Informatika, 2009)
Indonesia is a country that has the largest number of street children or children displaced, where they generally do not attend school or drop out of school. The influence of globalization is developing rapidly, and the technology is developing rapidly, the transfer of knowledge can be developed and the effect on the existing education system, both between countries and between nations. This can be seen from the reality of children education problems in Indonesia. Education is an effort the consciousness for the oppressed (poor children/street children), because only through education will be delivered for the exemption suppressed. Education can be the cause of the birth of their oppressed. Education became an important factor to open community awareness. Through education will the understanding oppressed causes for this and they will be able to even attempt to free the fetters oppressed.Key words: The Consciousness Theory, Solutions of Streets Children Education